The Zen of Web Discovery - (:unkn) unknown (My University, 2013)
Many libraries have revitalized their role by offering an updated resource discovery layer. This article gives an informal overview of design principles and best practices for implementing a web-scale discovery system. Emphasis is placed on the proper service philosophy of supporting a new technology, with open communications and evidence-based customization.
Keywords: Discovery Systems